Penanganan Special Cargo Domestik Oleh Unit Cargo Service Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Erangga Fradana; Faiz Albana (Journal of Creative Student Research, 2024)
In current cargo management operations, the process of loading and unloading incoming cargo still uses human power. The problems that occur at the Cargo Terminal are: There are a lot of cargo items that need to be handled, especially special types of cargo. There have been several incidents where cargo items were released outside operational hours and this resulted in the cargo not being handled properly. So special processing and handling is needed for the release of this special cargo because these goods are types of goods that are easily damaged, die, rot, wither and have high value. Therefore, the release process needs to have special procedures in accordance with IATA and/or carrier regulations. This research uses qualitative methods with descriptive research type. Researchers obtained data for this study at General Ahmad Yani International Airport, Semarang. Data collection from this research is interviews, observation and documentation. The results of this research show that the description of domestic special cargo handling at the Semarang cargo terminal can be defined as handling cargo goods that must be handled specifically or handled outside operational hours. Release of commodity type cargo (live animals, perishables, marine products) supported by personnel/officers who have competence in their fields.